Evaluation of digestively resistant or soluble fibers, short- and medium-chain fatty acids, trace minerals, and antibiotics in nonchallenged nursery pigs on performance, digestibility, and intestinal integrity. (21st September 2022) - Kerr, Brian J; Trachsel, Julian M; Bearson, Bradley L; Loving, Crystal L; Bearson, Shawn M D; Byrne, Kristen A; Pearce, Sarah C; Ramirez, Shelby M; Gabler, Nicholas K; Schweer, Wesley P; Helm, Emma T; De Mille, Carson M
Abstract: Three experiments (EXP ) were conducted to determine the effect of feed additives on performance, intestinal integrity, gastrointestinal volatile fatty acids (VFA ), and energy and nutrient digestion in nonchallenged nursery pigs. In EXP 1, 480 pigs (6.36-kg body weight, BW ) were placed into 96 pens with 5 pigs/pen, and allotted to 1 of 10 dietary treatments: 1) negative control containing no feed additive (NC ), 2) NC + 44 mg chlortetracycline and 38.5 mg tiamulin/kg diet (CT sb ), 3) NC + 5% resistant potato starch (RS po ), 4) NC + 5% soluble corn fiber (SCF ), 5) NC + 5% sugar beet pulp (SBP ), 6) NC + 0.30% fatty acid mix (FAM ), 7) NC + 0.10% phytogenic blend of essential oils and flavoring compounds (PHY ), 8) NC + 50 mg Cu and 1, 600 mg zinc oxide/kg diet (CuZn ), 9) NC + 5% resistant corn starch (RS cn ), and 10) NC + 0.05% β-glucan (BG ) for 28 d. There was no impact of dietary treatment on BW gain or feed intake ( P  ≥ 0.22). Pigs fed diets containing SCF, CTsb, and RSpo resulted in microbial community differences compared to pigs fed the NC ( P  < 0.05). In EXP 2, 48 barrows (12.8 kg BW) were selected at the end of EXP 1 and fed the same dietary treatments they had previously received: 1) NC, 2) NC + 5% RScn, 3) NC + 5% SCF, and 4) NC + FAM for 8 d. There was no effect of feeding diets containing RScn, SCF, or FAM on in vivo intestinal permeability ( P  ≤ 0.21). Ileal or colon pH, concentrations of VFA did not differ due to dietary treatment ( P ≥  0.36), but pigs fed diets containing FAM resulted in a greater butyric acid concentration in the cecum compared to pigs fed the NC ( P  ≤ 0.05). In EXP 3, 156 pigs (6.11 kg BW) were placed into 52 pens with 3 pigs/pen and allotted to 1 of 4 dietary treatments arranged in a factorial manner: 1) NC, 2) NC + 5% RSpo, 3) NC + 0.30% FAM, and 4) NC + 5% RSpo  + 0.30% FAM for 24 d. Feeding pigs diets containing RSpo did not affect BW gain ( P  = 0.91) while pigs fed diets containing FAM grew improved BW gain ( P  = 0.09). Colonic butyric acid concentrations were greater in pigs fed diets containing RSpo ( P  = 0.03), while pigs fed diets containing FAM exhibited reduced total VFA concentrations ( P  = 0.11). The results indicate that supplementing diets with digestively resistant but fermentable fibers, short- and medium-chain fatty acids, or antibiotics do not have a consistent effect, positive or negative, on markers of intestinal integrity or barrier function, intestinal VFA patterns, ATTD of energy and nutrients, or on pig performance. Abstract : Nonantibiotic in-feed additives have limited effects on performance, nutrient digestibility, and intestinal function when supplemented to diets fed to nursery pigs. Lay Summary: In-feed antimicrobials have been an important technology in swine production for protecting health and supporting growth. However, with legislative restrictions on the use of most antibiotics for growth promotion, research is needed to evaluate in-feed additives in replacing this growth promoting technology. Thus, strategies to enhance energy and nutrient digestibility, intestinal function and integrity, gastrointestinal volatile fatty acid concentrations, and microbial ecology in nursery pigs are desirable targets. The results of the three experiments conducted herein do not indicate that supplementing diets with digestively resistant but fermentable fibers, short-medium-chain fatty acids, or antibiotics have a consistent positive or negative effect on markers of intestinal integrity or barrier function, VFA patterns (ileal, cecal, or colon), ATTD of energy and nutrients, or pig performance.